2011
DOI: 10.1111/j.1365-3059.2011.02551.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Fusarium oxysporum and related species pathogenic on tomato in Algeria and other Mediterranean countries

Abstract: In order to characterize the pathogen(s) responsible for the outbreak of fusarium diseases in Algeria, 48 Fusarium spp. isolates were collected from diseased tomato in Algeria and compared with 58 isolates of Fusarium oxysporum originating from seven other Mediterranean countries and 24 reference strains. Partial sequences of the translation elongation factor EF1a gene enabled identification of 27 isolates as F. oxysporum, 18 as F. commune and three as F. redolens among the Algerian isolates. Pathogenicity tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
(55 reference statements)
0
33
0
Order By: Relevance
“…DNA sequences from the mtSSU or EF-1α regions were useful to distinguish F. commune from F. oxysporum on host plants of soybean, Douglas-fir, tomato, and horseradish (4,6,31,32). Phylogenetic analyses of the individual or the combined mtSSU and EF-1α sequences have identified F. commune as a sister taxon of F. oxysporum (4,6,31,32). The phylogenetic analyses of three regions (mtSSU, EF-1α, and IGS) in this study all indicated that F. commune is in a separate clade, clearly distinct from the FOSC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequences from the mtSSU or EF-1α regions were useful to distinguish F. commune from F. oxysporum on host plants of soybean, Douglas-fir, tomato, and horseradish (4,6,31,32). Phylogenetic analyses of the individual or the combined mtSSU and EF-1α sequences have identified F. commune as a sister taxon of F. oxysporum (4,6,31,32). The phylogenetic analyses of three regions (mtSSU, EF-1α, and IGS) in this study all indicated that F. commune is in a separate clade, clearly distinct from the FOSC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The roots were then wounded with a sterile knife, immersed in a spore suspension (1 9 10 6 spores/mL) for 5 min, swirled several times and transplanted into pots containing 4 kg sterilized soil mixture (3:2:1 v/v ratio of top soil-peat moss-sand). After transplanting, each pot was inoculated by drenching the soil around the crown with 200 mL of the same spore suspensions (1 9 10 6 spores/ mL) used for root infection (Edel-Hermann et al 2011). As a control, roots were wounded and dipped in distilled water, transplanted into pots with sterilized soil and treated with 200 mL sterilized distilled water.…”
Section: Pathogenicity Testmentioning
confidence: 99%
“…They have revealed the high level of phylogenetic diversity within several morphological species such as F. oxysporum and Fusarium solani, which are now recognized as species complexes. Among useful loci, the translation elongation factor 1-alpha (EF-1α) gene allowed both to differentiate closely related species and to reveal intraspecific polymorphism (O'Donnell et al, 2009(O'Donnell et al, , 2012Edel-Hermann et al, 2012) and can be used as a BLAST query against the FUSARIUM-ID sequence database (Geiser et al, 2004) or the Fusarium MLST database (O'Donnell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%